Uninterrupted Connectivity Using Conditional Time Split Energy Extraction With Beamforming System for Disaster Affected Wireless Networks - K. Ashok; T. Sudha (IEEE Access, 2020)
The use of MIMO networks in wireless communication results in increased data rate but leads to severe interference issues and power losses. Promising beamforming (BF) architecture with Conditional Time split-Energy Extraction (CT-EE) is proposed to maximize the Energy Efficiency while optimizing the Mean Square Error (MSE) and Achievable Sum Rate (ASR). A distributed BF system using Minimum Mean Square Error algorithm is jointly implemented at all cooperating nodes. Energy Extraction (EE) from RF signal at the relay nodes facilitates full connectivity among the users. The signal transmission and EE phases are jointly implemented using time-split architecture, without using fixed pre-assigned time slots. Time split from information decoding to EE phase is done only if the battery life is found to be critical. The paper investigates the scope of bypassing the EE phase after ensuring the required power level. The performance of the proposed architecture is compared with the conventional BF and existing EE methods in terms of MSE, ASR and energy efficiency. The proposed architecture is well suitable to establish uninterrupted connectivity between user nodes which are frequently used and have severe power drain-off issues as they can be a part of natural disaster like flood affected wireless networks.